2023
DOI: 10.3390/jmse11091761
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Evaluation and Validation of Pressure Distributions in Ice–Structure Collisions Using a Pendulum Apparatus

Ho-Sang Jang,
Se-Yun Hwang,
Jang Hyun Lee

Abstract: This study introduced an experimental setup designed to predict collision pressure exerted on a structure due to ice impacts. The primary aim was to forecast the pressure distribution and structural behavior following an ice collision on a laboratory scale. The apparatus comprises a double-pendulum system situated within a cold chamber, facilitating the prediction of collision forces by varying both the collision energy and velocity. Experiments were conducted at collision velocities of 5, 7, and 10 knots, rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…Throughout this process, multiple FEA iterations were undertaken to determine previously undefined material constants. According to the quasi-static compression test results reported by Jang et al [16], it was observed that ice specimens, configured as square columns with cross-sectional dimensions of 100 mm × 100 mm and a height of 250 mm, failed under loads ranging from approximately 25 to 32 kN when compressed by 5 mm (Error! Reference source not found.…”
Section: Finite Element Analysis Simulating Ice Compression Experimentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Throughout this process, multiple FEA iterations were undertaken to determine previously undefined material constants. According to the quasi-static compression test results reported by Jang et al [16], it was observed that ice specimens, configured as square columns with cross-sectional dimensions of 100 mm × 100 mm and a height of 250 mm, failed under loads ranging from approximately 25 to 32 kN when compressed by 5 mm (Error! Reference source not found.…”
Section: Finite Element Analysis Simulating Ice Compression Experimentsmentioning
confidence: 99%
“…In this study, the collision pendulum experiment conducted by Jang et al [16] was chosen for numerical simulation. A detailed discussion on the material models associated this simulation is provided in Sections 2, 3.1, and 3.2.…”
Section: Overview Of the Ice-structural Collision Simulation Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The plastic deformation and energy absorption of a plate and the collision forces during the impact process were studied. Jang et al [14] designed an experimental set-up, including a double-pendulum system situated within a cold chamber, which can predict the collision forces under ice impacts by varying both the collision energy and velocity. Considering the influence of fluid motion on ship-ice impact, Kim et al [15] carried out a series of laboratory-scale tests of freshwater granular ice blocks against stiffened steel panels in the ice tank and analyzed the impact force and the permanent plate deformations of the structure.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 5 is a diagram to introduce the theoretical model of the dynamic response of ice floe-plate impact. (14) can be used to obtain the maximum plastic deformation wm and the maximum impact force Fm of the plate under rigid-mass impact.…”
Section: Introduction To the Proposed Theoretical Modelmentioning
confidence: 99%